Factors Associated With Ari Disease in Toddlers at Desa Lumbutarombo, Banawa Selatan District, Donggala Regen - Hijrah, Hijrah; Budiman, Budiman; Nur, Andi Reza Alief Chairun (International Journal of Health, Economics, and Social Sciences (IJHESS), 2021)
Acute Respiratory Infection (ARI) is an acute infection that attacks one part and or more of the respiratory tract starting from the nose (upper tract) to alveoli (lower tract) including tissue adenexes, such as the sinuses, middle ear cavity, and pleura. The purpose of this study was to determine the factors associated with is a disease in children under five, consisting of smoking in the house, romanization, and the use of biomass cooking fuel. This isÂ  Analytical survey research with an approach cross-sectional. This research was conducted in Desa Lumbutarombo, Banawa Selatan District, Donggala Regency in February until March 2020, with a sample of 66 respondents. The results showed that there was a correlation between smoking in a clean water supply house and ARI in children under five as evidenced by statistical tests with a p-value of 0.039 <0.05. The results showed that there was a correlation between roomization and ARI in children under five as evidenced by statistical tests with a p-value of 0.000 <0.05. The results showed that there was no correlation between the use of biomass cooking fuel and ARI in children under five as evidenced by statistical tests with a p-value of 0.275> 0.05. This is hoped that the government and health workers and the community in Lumbutarombo Village will always protect the surrounding environment and conduct health service surveys and conduct counseling so that it can reduce the risk of ARI disease.